The Theology of Industrialization: A Hermeneutic Analysis of Production Ethics in Surah Al-Hadid Verse 25 - Riza Wahyu Rahmanda; Diana Wulandari; Achmad Basofitrah; Safa Salsabila Kurnia Widayanti; Imelda Musarofah (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2025)
This study examines the meaning of production in Surah Al-Hadid verse 25 from the perspective of Islamic economics using a qualitative library research approach. The research is motivated by the dominance of materialistic production paradigms that often neglect ethical and social dimensions. Data were collected from classical and contemporary tafsir literature, as well as scholarly works in Islamic economics, and analyzed using descriptive-analytical and content analysis methods. The findings reveal that production in the Qur’anic perspective is not merely an economic activity but a value-driven process grounded in justice, balance, responsibility, and public welfare (maslahah). The verse symbolically links productive power with moral accountability, emphasizing that economic activities must align with social justice and ethical conduct. However, variations in interpretation arise due to differences in methodological approaches, theoretical orientations, and disciplinary backgrounds. This study contributes by offering an integrative framework that bridges normative tafsir and contemporary economic analysis. It highlights the need to contextualize Qur’anic teachings to address modern production challenges. The study suggests that production in Islamic economics should incorporate ethical values to achieve sustainable and equitable development.